Chapter La cittadinanza come politica pubblica tra ius sanguinis, ius soli e ius culturae - Corsi, Cecilia (Studi e saggi, 2023)
The contribution aims to offer a critical analysis of the Italian discipline on the ways of acquiring citizenship. The paper analyzes the most problematic aspects of the 1992 law, showing its anachronisms and unreasonableness, and then highlights the profiles that most need reform. In particular, the status of the minor born or schooled in Italy and the naturalization procedure claim a profound revision.